Microwave-assisted solution–liquid–solid growth of Ge1−xSnx nanowires with high tin content1. Issue 61 (7th August 2015) - Barth, Sven; Seifner, Michael S.; Bernardi, Johannes
<x xml:space="preserve">Abstract</x> The first bottom-up synthesis of Ge1−xSnx nanowires with a high tin content of 12.4 ± 0.7 at% was developed.